2010
DOI: 10.1080/03630242.2010.480905
|View full text |Cite
|
Sign up to set email alerts
|

Perpetuating “Scientific Motherhood”: Infant Feeding Discourse in Parents Magazine, 1930-2007

Abstract: Although breastfeeding initiation rates have recently been at an all-time high, duration continues to be considerably low. Given the health benefits associated with extended breastfeeding, this discrepancy is cause for concern. This research examined the messages conveyed about infant feeding in a popular parenting magazine, Parents magazine, from 1930 through 2007. Findings indicated that the messages about infant feeding shifted in accordance with changing ideologies about the means of infant feeding-from bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…In a magazine article published in 1934 titled, "Feeding the new baby," Regina J. Woody, describes the experience of bringing an infant home from the hospital. Woody writes, "Once you are at home and the baby safely tucked into his little crib, you will be confronted, almost immediately, with the practical necessity of warming and giving some of the formula which the hospital has so kindly provided" p9 [57].…”
Section: A Cross-cultural and Historical View Of Infant Sleepmentioning
confidence: 99%
“…In a magazine article published in 1934 titled, "Feeding the new baby," Regina J. Woody, describes the experience of bringing an infant home from the hospital. Woody writes, "Once you are at home and the baby safely tucked into his little crib, you will be confronted, almost immediately, with the practical necessity of warming and giving some of the formula which the hospital has so kindly provided" p9 [57].…”
Section: A Cross-cultural and Historical View Of Infant Sleepmentioning
confidence: 99%
“…This blameless recipient was herself an innocent victim who through no fault of her own was physically incapable of producing her own 'liquid gold'. This 'moral mother' used medical experts to weigh potential risks of each form of infant feeding, and managed risk through expert guidance and informed choice (Apple, 1995(Apple, , 2006Faircloth, 2010Faircloth, , 2013Foss, 2010;Knaak, 2010). Such mothers were officially approved by a representative of the broader (medico-scientific) social order who certified the worthiness of the recipient, as breast milk from a bank could only accessed with a physician prescription.…”
Section: Discussionmentioning
confidence: 99%
“…Within the ideology of intensive mothering, the 'scientific mother' is expected to rely on scientific research to support parenting decisions; parenting choices are considered 'morally righteous' if they can be supported by scientific research, which mothers are expected to use appropriately (Apple, 1995(Apple, , 2006Faircloth, 2010Faircloth, , 2013Foss, 2010;Hammer & Inglin, 2014;Knaak, 2010). Researchers have found that that mothers do approach decisions about feeding their babies rationally; assessing risks in their decisions to breastfeed (Knaak, 2010;Lee 2007Lee , 2008 or to share milk (Gribble, 2014) or when selecting one formula over another (Afflerback, Carter, Anthony, & Grauerholz, 2013).…”
Section: Milk Sharing Mothering and Riskmentioning
confidence: 99%
“…Media images of celebrities breastfeeding are relatively rare compared with representations of non-celebrity breastfeeding (Brown and Peuchaud 2008;Foss 2010;Leah Frerichs, Julie L. Andsager, Shelly Campo, Mary Aquilino, and Carolyn Stewart Dyer 2006;Lesley Henderson, Jenny Kitzinger, and Josephine Green 2000). In the last fifteen years, only one high-circulation US magazine cover besides Jolie's W photo has featured an image of celebrity breastfeeding.…”
Section: Intimacy On Display: Maternal Celebrity Bodies In the Mediamentioning
confidence: 97%